Cinema, memória e ditadura civil-militar: representações sobre as juventudes em O que é isso, Companheiro? e Batismo de sangue - Noronha, Danielle Parfentieff de (2013)
In this work I analyze the representations about youth from the corresponding period of the civil-military dictatorship in Brazil (1964-1985) in the narratives of contemporary Brazilian cinema, from an ethnography of the films O que é isso Companheiro? (Bruno Barreto, 1997) and Batismo de Sangue (Helvécio Ratton, 2007). I introduce the discussion between fiction and reality in cinema, which can create, modify or reinforce the imaginary about who were that youth, and still build imaginative discourses about the nation in the dictatorial period, and thus reformulate the social memory of that period. I understand cinema as language, which bears a complex relationship between author and audience with several possibilities for analysis and interpretation. In this sense, I consider the links between art and life, and thus between language and speech, and also as representations of memory and nation